Management of Pregnancy in a Patient with Severe Hemophilia Type A - Vipra Sharma; Aysha Khalid; Alice J. Cohen (Thieme Medical Publishers, Inc., 2013)
Abstract Hemophilia type A is a rare inherited bleeding disorder with a diversity of clinical manifestations ranging from persistent bleeding after minor trauma, spontaneous deep muscle or joint hemorrhage, to intracranial hemorrhage. As an X-linked disorder, hemophilia is rare in females and therefore there is little experience with pregnancy and no standardized guidelines to prevent bleeding antepartum, at delivery, and postpartum. We report the clinical course and management of a woman with severe hemophilia A who on two occasions had uncomplicated pregnancies and vaginal deliveries at term utilizing bolus recombinant factor VIII concentrate.